2022
DOI: 10.1186/s12913-022-08537-7
|View full text |Cite
|
Sign up to set email alerts
|

Employment status of AFROHUN-Uganda one health alumni, and facilitators and barriers to application of the one health approach: a tracer study

Abstract: Background The One Health (OH) approach integrates multiple competencies in the prevention and control of disease outbreaks. Through a range of OH competence-based activities, the Africa One Health University Network (AFROHUN) built the capacity of selected students at Makerere University and Mbarara University of Science and Technology. This study applied the Systems Theoretical Framework (STF) of career development to establish the employment status of AFROHUN-Uganda alumni, and the facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This study revealed a high absorption rate of alumni into the workforce. A similar absorption rate was recently reported in the same setting [6], but a lower rate has been reported in a similar setting among a more diverse population of One Health alumni [7,16]. This reflects a growing focus on, and higher demand for, specialized health workers in the country to counteract the negative consequences of task-shifting [17].…”
Section: Employment Ratessupporting
confidence: 73%
“…This study revealed a high absorption rate of alumni into the workforce. A similar absorption rate was recently reported in the same setting [6], but a lower rate has been reported in a similar setting among a more diverse population of One Health alumni [7,16]. This reflects a growing focus on, and higher demand for, specialized health workers in the country to counteract the negative consequences of task-shifting [17].…”
Section: Employment Ratessupporting
confidence: 73%
“…The study revealed a good absorption rate of alumni into the workforce. A lower absorption rate has been reported in a similar setting but among a more diverse population of one healthy alumni [1,15]. In addition, the majority of the respondents in employment were in the public sector, yet the private sector is the largest employer in Uganda.…”
Section: Career Paths By the Alumnimentioning
confidence: 77%